PENGARUH LATIHAN MULTIPLE BOX TO BOX JUMP WITH SINGLE LEG LANDING TERHADAP KECEPATAN TENDANGAN DEPAN - Nune Wire PanjiSakti; Muhammad Satria Mulyajaya (Universitas Pendidikan Mandalika, 2017)
In extracurricular pencak silat of Tapak Suci SMAN 1 Gunungsari after observation, the researcher found that the low level of students' kick ability, found the kickback speed of martial arts athletes SMAN 1 Gunungsari very low, weak seen from the frequency of kicks done in every round average 3-5 times. Thus, the aspect of these skills becomes absolute controlled by the martial arts athletes in the process of coaching to a higher level can be sustainable. Relation with this on extracurricular pencak silat Tapak Suci SMAN 1 Gunungsari, that the low ability of students can be caused because the training method provided only limited to the improvement of basic motion techniques. The problem revealed from this research is